A field guide to eukaryotic circular single-stranded DNA viruses: insights gained from metagenomics - Rosario, Karyna; Duffy, Siobain; Breitbart, Mya (Archives of virology, 2012)
Despite their small size and limited protein-coding capacity, the rapid evolution rates of single-stranded DNA (ssDNA) viruses have led to their emergence as serious plant and animal pathogens. Recently, metagenomics has revealed an unprecedented diversity of ssDNA viruses, expanding their known environmental distributions and host ranges. This review summarizes and contrasts the basic characteristics of known circular ssDNA viral groups, providing a resource for analyzing the wealth of ssDNA viral sequences identified through metagenomics. Since ssDNA viruses are largely identified based on conserved rolling circle replication proteins, this review highlights distinguishing motifs and catalytic residues important for replication. Genomes identified through metagenomics have demonstrated unique ssDNA viral genome architectures and revealed characteristics that blur the boundaries between previously well-defined groups. Metagenomic discovery of ssDNA viruses has created both a challenge to current taxonomic classification schemes and an opportunity to revisit hypotheses regarding the evolutionary history of these viruses.